“Spontaneous pneumomediastinum in primary Sjogren's syndrome: An uncommon manifestation” - Viswesvaran Balasubramanian; Shibdas Chakrabarti; Abhijeet Singh; Nitesh Gupta (Indian Journal of Rheumatology)
Sjogren's syndrome (SS) is the second most common autoimmune disorder, after rheumatoid arthritis that affects predominantly middle-aged women. Pulmonary involvement in SS can manifest as airway abnormalities, interstitial lung disease (ILD), and lymphoproliferative disorders. Spontaneous pneumomediastinum has been reported in ILD associated with various connective tissue diseases, most frequently inflammatory myopathies (dermatomyositis or polymyositis). However, the occurrence of spontaneous pneumomediastinum in SS is uncommon. We report a rare occurrence of spontaneous pneumomediastinum in a patient with primary SS.